1988
DOI: 10.1063/1.100601
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial barium hexaferrite on sapphire by sputter deposition

Abstract: Epitaxial films of barium hexaferrite (BaFe12 O19 ) have been prepared on basal-oriented sapphire substrates by rf sputter deposition of an amorphous ferrite film and crystallization of the film by annealing. Liquid phase epitaxy has been used to deposit an additional barium hexaferrite layer on top of the sputter deposited and annealed film. In this way films having symmetric ferromagnetic resonance peaks as narrow as 41 Oe at 60 GHz have been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…2,3 As mentioned earlier, our study on amorphous fused quartz and Si͑111͒ substrates showed that the films prepared on two substrates under similar conditions showed similar properties. 17,18 To further check this point we show a comparative study of the films deposited on different kinds of substrates.…”
Section: The Effect Of Substrate Materialsmentioning
confidence: 59%
See 2 more Smart Citations
“…2,3 As mentioned earlier, our study on amorphous fused quartz and Si͑111͒ substrates showed that the films prepared on two substrates under similar conditions showed similar properties. 17,18 To further check this point we show a comparative study of the films deposited on different kinds of substrates.…”
Section: The Effect Of Substrate Materialsmentioning
confidence: 59%
“…M -type barium ferrite ͑BaM͒ films with c-axis oriented normal to the film plane have been reported by different workers. [1][2][3][4][5][6][7][8][9] These films have been deposited using different deposition techniques such as dc and rf diode sputtering, targets facing type sputtering, laser ablation, etc. 4 -7 These films have been crystallized either by in situ heating of substrates or postdeposition annealing of the films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,9,10,31,35,36 Sapphire is chosen because it has a rhombohedral crystal structure (a=5.128 Å and =5522′) which is close to the hexagonal structure of BaM; 31 and the mismatches of the lattice parameters and thermal expansion coefficients between sapphire and BaM materials are relatively small. 7,31,36 Certain device applications, however, require the growth of BaM films on conductive substrates. In coupled-line and stripline-type devices, for example, a ground plane is needed underneath the active layer.…”
Section: Deposition Of Bam Thin Films On Metallic Electrodesmentioning
confidence: 99%
“…30 A variety of different techniques have been used to fabricate BaM film materials. These include pulsed laser deposition (PLD), 7,8,9,10,11,12,28,31 liquid phase epitaxy (LPE), 32,33,34,35 RF magnetron sputtering, 36,37,19,38,39,40 molecular beam epitaxy (MBE), 14 metallo-organic decomposition (MOD), 15 chemical vapor deposition (CVD), 41 and screen printing. 16,17 The device demonstration includes both numerical 20,21,22 and experimental efforts.…”
Section: Introductionmentioning
confidence: 99%